2009
DOI: 10.1158/1078-0432.ccr-08-1564
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genome-Wide DNA Copy Number and Expression Analysis Identifies Distinct Mechanisms of Primary Chemoresistance in Ovarian Carcinomas

Abstract: Purpose: A significant number of women with serous ovarian cancer are intrinsically refractory to platinum-based treatment. We analyzed somatic DNA copy number variation and gene expression data to identify key mechanisms associated with primary resistance in advancedstage serous cancers. Experimental Design: Genome-wide copy number variation was measured in 118 ovarian tumors using high-resolution oligonucleotide microarrays. A well-defined subset of 85 advanced-stage serous tumors was then used to relate cop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
247
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 267 publications
(264 citation statements)
references
References 49 publications
15
247
2
Order By: Relevance
“…Our recent results indicate that Dex could enhance cell adhesion by increasing the expression of some ECM components, such as collagen I and hyaluronic acid, in . This finding is in line with the latest report that the enhanced ECM deposition may play a direct role in primary chemoresistance in ovarian carcinoma (Etemadmoghadam et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…Our recent results indicate that Dex could enhance cell adhesion by increasing the expression of some ECM components, such as collagen I and hyaluronic acid, in . This finding is in line with the latest report that the enhanced ECM deposition may play a direct role in primary chemoresistance in ovarian carcinoma (Etemadmoghadam et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…2-7 Several studies on gene profiling of the primary tumor using microarray technology have described potential genes/pathways contributing to chemotherapy resistance and their association with risk stratification/overall survival. [8][9][10][11][12][13][14][15][16][17][18] Unlike the clinical impact of gene profiling on treatment decisions for several solid tumors there has been limited progress with the prediction or the clinical management of recurrent HGSOC.Studies with recurrent ovarian tumors 19 have described surgical and second-line chemotherapy options for the clinical management of the disease. Chromosomal aberrations associated with risk for recurrence have been identified by using comparative genomic hybridization (CGH) analysis.…”
mentioning
confidence: 99%
“…The association between cyclin E amplification and poor outcome has also been identified in recent German and Japanese studies, although the correlation was not statistically significant in the latter (Mayr et al 2006, Nakayama et al 2010. Two independent labs have also suggested that amplification of the cyclin E gene was associated with primary treatment resistance and targeting cyclin E expression with siRNA reduced cell viability and increased apoptosis (Etemadmoghadam et al 2009, Nakayama et al 2010. These studies suggest that cyclin E amplification/expression may serve as both a prognostic and predictive factor in ovarian cancer as well as a therapeutic target in the treatment of ovarian cancer.…”
Section: Cell Cycle Regulatory Proteinsmentioning
confidence: 77%